Síntese de cromenonas via reações de ciclização intramolecular de alquinilarilcetonas mediada por tiol - Heck, Ritiele (2020)
Due to the great relevance of chromenone derivatives in pharmacology, and consequently in organic synthesis, an efficient methodology was developed for the synthesis of 4H-chromen-4-ones derivatives through intramolecular cyclization of alkynyl aryl ketones in the presence of PhSH (1 equiv), NaOH (5 mol%) as base, using NMP (1 mL) as solvent, at reflux temperature (202 ºC) in ambient atmosphere. Through this method, it became possible to obtain a series of 4H-chromen-4-ones comprising 15 examples with yields from 23 to 95%. This methodology presents advantages for the synthesis of 4H-chromen-4-ones, since the reaction conditions lead to a high regioselectivity, by furnishing only six-membered heterocycles, after 30 minutes, besides employing base catalytic amounts in absence of transition-metal salts as well as inert reaction ambient.